NMR Studies of Tau Protein in Tauopathies - Kitoka, Kristine; Skrabana, Rostislav; Gasparik, Norbert; Hritz, Jozef; Jaudzems, Kristaps (Frontiers in Molecular Biosciences, 2021)
Tauopathies, including Alzheimer’s disease (AD), are the most troublesome of all age-related chronic conditions, as there are no well-established disease-modifying therapies for their prevention and treatment. Spatio-temporal distribution of tau protein pathology correlates with cognitive decline and severity of the disease, therefore, tau protein has become an appealing target for therapy. Current knowledge of the pathological effects and significance of specific species in the tau aggregation pathway is incomplete although more and more structural and mechanistic insights are being gained using biophysical techniques. Here we review the application of NMR to structural studies of various tau forms that appear in its aggregation process, focusing on results obtained from solid-state NMR. Furthermore, we discuss implications from these studies and their prospective contribution to the development of new tauopathy therapies.